The Relationship Between Leadership And Teachers' Performance At State Vocational High SchoolL â€œXâ€ Bandung - Budihastuti, Eka Sari; Hamali, Arif Yusuf (Bina Nusantara University, 2016)
This research was conducted at State Vocational High School â€œXâ€ Bandung, aimed to determine theÂ relationship of leadership and teachersâ€™ performance, and also to analyze the effect of leadership on teachersâ€™Â performance at State Vocational High School â€œXâ€ Bandung. Respondents of this research are 30 employeesÂ selected by census technique. This research uses descriptive and associative method, which tests the connectionÂ using the Spearman Rank correlation analysis, and also done to determine the accuracy of measurement usingÂ by the validity and reliability test. Results of the validity and reliability test of variables X and Y are valid andÂ reliable. Calculations were performed using SPSS software version 19. The result of this study shows thatÂ leadership is in the category of good and teachersâ€™ performance is also in the category of good. Results showsÂ the correlation of leadership with teachersâ€™ performace at State Vocational High School â€œXâ€ Bandung based onÂ the interpretation of Pearson Product Moment correlation is in the criteria of strong. It shows that thehypothesis is proved, there is significant relationship between leadership and teachersâ€™ performance at StateÂ Vocational High School â€œXâ€ Bandung.